Study on Child Sexual Abuse Its Types, Causes and Effect: Understanding and Addressing Child Sexual Abuse in India: Findings, Risk Factors, and Implications for Educators (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Child sexual abuse (CSA) is a genuine and far reaching issue in India for what it's worth in numerous pieces of the present reality. The injury related with sexual abuse can add to captured improvement, just as a large group of mental and enthusiastic issues, that a few children and young people may never survive. At the point when sexual abuse goes unreported and children are not given the defensive and restorative help they need, they are left to endure peacefully. This article examines the nature and frequency of the sexual abuse of minors in India and presents an outline of examination discoveries to date. Socio-social and familial hazard factors associated with CSA are talked about. Basic side effects and issues related with sexual abuse are sketched out. At long last, a few ramifications for instructors working with children in India who have been explicitly abused are highlighted.